Assessment of earthquake locations in 3‐D deterministic velocity models: A case study from the Altotiberina Near Fault Observatory (Italy). Issue 11 (14th November 2016) - Latorre, D.; Mirabella, F.; Chiaraluce, L.; Trippetta, F.; Lomax, A.
Abstract: The accuracy of earthquake locations and their correspondence with subsurface geology depends strongly on the accuracy of the available seismic velocity model. Most modern methods to construct a velocity model for earthquake location are based on the inversion of passive source seismological data. Another approach is the integration of high‐resolution geological and geophysical data to construct deterministic velocity models in which earthquake locations can be directly correlated to the geological structures. Such models have to be kinematically consistent with independent seismological data in order to provide precise hypocenter solutions. We present the Altotiberina (AT) seismic model, a three‐dimensional velocity model for the Upper Tiber Valley region (Northern Apennines, Italy), constructed by combining 300 km of seismic reflection profiles, six deep boreholes (down to 5 km depth), detailed data from geological surveys and direct measurements of P and S wave velocities performed in situ and in laboratory. We assess the robustness of the AT seismic model by locating 11, 713 earthquakes with a nonlinear, global‐search inversion method and comparing the probabilistic hypocenter solutions to those calculated in three previously published velocity models, constructed by inverting passive seismological data only. Our results demonstrate that the AT seismic model is able to provide higher‐quality hypocenter locations than the previous velocity models. Earthquake locations are consistent with the subsurface geological structures and show a high degree of spatial correlation with specific lithostratigraphic units, suggesting a lithological control on the seismic activity evolution. Key Points: 3D deterministic velocity models from combined high‐resolution geological and geophysical data provide reliable earthquake locations Earthquakes located using these models allow a direct correlation between seismicity and geological structures The spatial correlation of earthquake locations with specific stratigraphic units suggests a lithological control on the seismic activity